CDR 2021
DOI: 10.20517/cdr.2021.35
|View full text |Cite
|
Sign up to set email alerts
|

ATP-binding cassette transporters at the zebrafish blood-brain barrier and the potential utility of the zebrafish as an in vivo model

Abstract: The brain is protected from toxins by a tightly regulated network of specialized cells, including endothelial cells, pericytes, astrocyes, and neurons, known collectively as the blood-brain barrier (BBB). This selectively permeable barrier permits only the most crucial molecules essential for brain function to enter and employs a number of different mechanisms to prevent the entry of potentially harmful toxins and pathogens. In addition to a physical barrier comprised of endothelial cells that form tight junct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 85 publications
2
4
0
Order By: Relevance
“…S1). This result indicates that the BBB of zebra sh embryo at 3 dpf is permeable, which agrees with previous studies that the BBB is functionally immature at 3 dpf [13,25]. Interestingly, images of injected embryos after 1.5 hours of circulation showed that the level of rhodamine123 remaining in the parenchyma of Tg[ k1:EGFP];abcb4 −/− was signi cantly higher than that of Tg[ k1:EGFP] (Fig.…”
Section: Resultssupporting
confidence: 91%
“…S1). This result indicates that the BBB of zebra sh embryo at 3 dpf is permeable, which agrees with previous studies that the BBB is functionally immature at 3 dpf [13,25]. Interestingly, images of injected embryos after 1.5 hours of circulation showed that the level of rhodamine123 remaining in the parenchyma of Tg[ k1:EGFP];abcb4 −/− was signi cantly higher than that of Tg[ k1:EGFP] (Fig.…”
Section: Resultssupporting
confidence: 91%
“…Zebrafish brain endothelial cells have many of the same adaptations as their mammalian counterparts. In addition, they possess homologs for the claudin family of transmembrane tight junction proteins found in mammals that contribute to BBB permeability [ 20 ].…”
Section: General Anatomy Of the Teleost Fish Brain And Neurovascular ...mentioning
confidence: 99%
“…ABC transporters, which are significant players in the multidrug-resistant phenotype of glioma and other malignancies, efflux several chemotherapeutics [ 38 ]. As a result, many efforts have been made to improve tumor drug delivery by using competitive or non-competitive inhibitors, and many P-gp and BCRP inhibitors, such as valspodar [ 39 ], dexverapamil [ 40 ], tariquidar [ 41 ], biricodar [ 40 ], and elacridar, have been clinically evaluated for use as adjuvants on chemotherapy to treat non-brain tumors, as well as indirect inhibition by anti-P-gp monoclonal antibodies. Their effectiveness in overcoming the BBB has been tested in both animals and humans.…”
Section: General Background On the Blood–brain Barriermentioning
confidence: 99%